Once again about the meaning of the term “manubiae” - Rastegaeva, Mariya Nikolaevna (Античный мир и археология, 2022)
The article is devoted to the analysis of the term “manubiae” in the context of the construction activity of magistrates in ancient Rome. The author's arguments show that neither ancient sources nor historiography can resolve the dispute about war booty and manubial construction. Therefore, the author of the article proposes a different solution to the problem – in order to determine what manubiae is, how it differs from praeda, how and who could use manubiae, it is necessary to consider some property embezzlement claims by Roman generals (i.e. how and who could not use manubiae and on what grounds the Roman Senate could accuse duces of peculatus during the Rebuplic period). In conclusion, the definition of manubiae is given as part of the spoils of war, which was at the disposal of the generals.